Chemical Sciences in the Focus. Volume 2, - Adeniyi, Adeleke; Adewuyi, Sheriff; Amadou Condé, Sékou; Amara Konaté, Ahmed; Canal, John P.; Chaichamni, Punnita; Chinda, Kechinyere; Constance Béavogui, Marie; Ejeromedoghene, Onome; Ezeali Ali, Ewa; Giwa, Olayiwola; Gouado, Inocent; et al. (Chemical Sciences in the Focus, 2021)
Based on "The Virtual Conference on Chemistry and its Applications (VCCA-2020) - Research and Innovations in Chemical Sciences: Paving the Way Forward" held in August 2020 and organized by the Computational Chemistry Group of the University of Mauritius. The chapters reflect a wide range of fundamental and applied research in the chemical sciences and interdisciplinary subjects.